DEMONSTRATING THE EFFECT OF PARENT’S ROLE IN EARLY CHILDHOOD CHARACTER EDUCATION - Kola Kiran Kumar, Dr. Santosh Jagwani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The objective of the study is to describe what values may be internalized to a family since early childhood. The findings demonstrate that children's character education should start from inside the home, because family is the smallest unit of society and it will depend on parents to teach children from early age. The method of this investigation was ex-post facto research. The populations in this study were parents and children in kindergarten of India. Samples from the population were consisted of 157 Parents. Instruments employed in this research were observations and questionnaires. Meanwhile the data analysis was carried out by employing specific methodologies which was Inferential Statistics with multiple regression analysis. These results revealed that the role of attention, affection, and security offered by parents directly influences the character education of early infancy.